Nutritional status of high yielding crossbred cow around parturition - Yousuf, Mohammad; Alam, Mohammad Rashedul; Shaikat, Amir Hossan; Faruk, Md. Shohel Al; Saifuddin, A. K. M.; Ahasan, A. S. M. Lutful; Islam, Kamrul; Islam, S. K. M. Azizul (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The objective of this study was to evaluate nutritional status of high yielding dairy cattle around parturition. Materials and methods: Nutritional status of cows around the peri-parturient period was investigated for six months in dairy farm. Seven to eight months pregnant cows were selected for this study. Blood samples from 24 randomly selected cows were collected at stage-1, -2 and -3. The serum was stored at -20ºC until analyzing glucose, total protein (TP), albumin (Alb), triglycerides (Tg), cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL), calcium (Ca), magnesium (Mg) and phosphorus (P). Results: An increasing trend of glucose level was evidenced (P=0.07) during stage-1. Instead, higher levels of TP were found during stage-3 as compared to the stage-1 and -2. The Alb levels differed significantly (P<0.01) among different stages. A significantly increased (P<0.01) cholesterol, Tg, and HDL were found after parturition (stage-2 and -3) than before parturition (stage-1). LDL was significantly (P=0.02) increased during stage-2 and -3. A significantly higher level of Ca (P<0.01), Mg (P<0.01) and P (P=0.03) were present during stage-1. Glucose, TP, cholesterol and Tg were significantly higher (P<0.01) in cows two months after parturition, while Alb was found to be the highest (P<0.01) in cows immediately after parturition. An increasing trend of LDL (P=0.07) and HDL (P=0.07) were found in the cows two months after parturition. However, Ca levels were significantly (P=0.04) higher in cows two months after parturition. Conclusion: The results indicate that there is alteration of biochemical levels among the study population at three different stages, and these data may be helpful in using the necessary nutrients to the the high yielding cows around their parturition. http://dx.doi.org/10.5455/javar.2016.c134